Perancangan Aplikasi Presensi Di PT. Herlyk Ekspress Berbasis Web - Vani, Vani Ayu Anastasya; Maulana, Haisyam (JATISI, 2024)
Attendance is a must, especially within the scope of private or state companies, including PT. Herlyk Ekspress is engaged in the delivery of goods with quite a large number of employees in its various branches. Currently, the attendance process is still done manually, so an electronic system is needed to record employee attendance accurately and efficiently. The design of this system involves data collection, analysis, surveys, and implementation using several programming languages to manage the database. The result of this design is the creation of a real-time web-based attendance application using camera and GPS methods in several subsidiaries. It is hoped that this application will bring changes to the attendance process, increase efficiency in obtaining employee attendance information, and make it easier for service admins and leaders to manage employee attendance data.